2011
DOI: 10.1128/jb.00201-11
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Electron Transport Pathway for Graphene Oxide Reduction by Shewanella oneidensis MR-1

Abstract: We determined that graphene oxide reduction by Shewanella oneidensis MR-1 requires the Mtr respiratory pathway by analyzing a range of mutants lacking these proteins. Electron shuttling compounds increased the graphene oxide reduction rate 3-to 5-fold. These results may help facilitate the use of bacteria for large-scale graphene production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(70 citation statements)
references
References 22 publications
2
66
1
1
Order By: Relevance
“…† These inorganic elements originated from the soil minerals. 3,19,28 The mechanism underlying the bacterial transformation of PGO involves reduction during bacterial respiration for Shewanella and glycolysis for Escherichia coli, and PGO acts as a terminal electron acceptor in the reduction processes. 12 Fig.…”
Section: Changes In Surface Chemical Groupsmentioning
confidence: 99%
“…† These inorganic elements originated from the soil minerals. 3,19,28 The mechanism underlying the bacterial transformation of PGO involves reduction during bacterial respiration for Shewanella and glycolysis for Escherichia coli, and PGO acts as a terminal electron acceptor in the reduction processes. 12 Fig.…”
Section: Changes In Surface Chemical Groupsmentioning
confidence: 99%
“…Recently, graphene oxide was presented as another target for extracellular respiration (35,78). The reduction of graphene oxide is typically part of the graphene production process.…”
Section: Extracellular Electron Acceptorsmentioning
confidence: 99%
“…Furthermore, several different laboratories have demonstrated that mutants in mtrC, mtrB or mtrA are unable to grow with Fe(III) citrate as electron acceptor (Beliaev & Saffarini, 1998;Beliaev et al, 2001;Borloo et al, 2007;Hartshorne et al, 2009;Myers & Myers, 2002b). MtrA, MtrB and MtrC build the electron conduit to the cell surface, and MtrC is probably the most influential terminal reductase for extracellular respiration in S. oneidensis (Belchik et al, 2011;Beliaev et al, 2001;Jiao et al, 2011;Marshall et al, 2006;Reardon et al, 2010). All this seems to be in disagreement with the experiments conducted by Qian and co-workers.…”
Section: Discussionmentioning
confidence: 99%